The ARVi Learning App Makes Viruses Visible - Risda Putri Indriani; Tri Handayani Kurniati; Rizhal Hendi Ristanto (Journal of Science Learning, 2024)
In biology learning, the object of a virus cannot be seen directly. Augmented reality (AR) technology can help visualize the object of a virus in 3D, making it easier for students to learn about viruses. Therefore, this research aims to develop an AR-based learning media product called ARVi. ARVi was created using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The results of the analysis revealed that students need learning media with engaging visualizations. Therefore, ARVi was designed as a mobile application with various colors, images, videos, AR, and quizzes. ARVi underwent validation tests by experts, including biology education lecturers and biology teachers. The user responses were evaluated through a small group test involving 20 students, where questionnaires were distributed. Based on the questionnaire results, the average score for the media expert was 3.84, and for the material expert was 3.80. These scores indicate that ARVi is very valid for use as a learning medium. The results of the small group test were 2.85, indicating that ARVi is valid for use after minor revisions are made. The implementation results for 60 students, as determined through a paired t-test, showed a significant difference between the pretest and posttest results, with the posttest score being higher than the pretest score. The research results concluded that ARVi is suitable as a biology learning media.